"Self-Concept" Consideration Related to War Captivity for Iraqi Former Prisoners of Iraq-Iran War 1980-1988 - Maan Hameed (Iraqi National Journal of Nursing Specialties, 2023)
This descriptive study had begun from June 4th, 2006 and finished on September 15, 2006. Purpose: To know the changes in self-concept amongst Iraqi former prisoners of Iraq-Iran war, and the relationship with certain variables. Methodology: The sample was collected accidentally of 300 Iraqi former prisoners of war (POW) who were visiting: Ministry of Health and Ministry of Human rights. For collecting the information for this study, a questionnaire was constructed, this constructed questionnaire consisted of two parts: firstly, demographic data, which consists of six items and secondly; (13 items) which through them, we determine the self-concept in repatriates. Reliability and validity for this questionnaire were determined through the pilot study and the experts. Data were collected through using the questionnaire and by the interview technique. Data were analyzed by the application of descriptive statistical analysis, which were; percentages, frequencies, and inferential statistic analysis (Pearson correlation coefficient). Result: The study disclosed that 66.5% of those repatriates have good and moderate levels for the selfconcept, and the study disclosed also that there is a high significant relationship between the self- concept and, level of education and significant relationship with; duration of captivity, age at capture. military rank, and date of repatriation. Recommendation: This study recommends concentrating efforts through the centers, for restoring the confidence within themselves and with the community to achieve a rapid return and to maintain the psychological, medical and social support.